The Relationship Between Compulsive Buying and Hoarding in China: A Multicenter Study - He, Heping; Zhu, Meihua; Lam, Simon Ching (Frontiers in Psychology, 2021)
No previous research that explored the correlation between compulsive buying and hoarding in Chinese population as its focus. This study aims to determine the relationship between compulsive buying and hoarding in a nationally sample of the Chinese population comprising mainland Chinese (emerging economies) and Hong Kong (developed economies) participants. Self-reported measures consisting of demographic questions, Chinese version of Hoarding Rating Scale (CHRS), and Richmond Compulsive Buying Scale-Traditional Chinese (RCBS-TC) were administered to participants. After data collection, common method biases were precluded. The RCBS-TC and CHRS were validated by confirmatory factor analysis and found correlated by Pearson correlation coefficient. The RCBS-TC and CHRS demonstrated satisfactory levels of internal consistency (Cronbach’s α=0.872 and 0.828, respectively). A three-factor model, including hoarding, obsessive-compulsive, and impulse-control disorders, was obtained through CFA with satisfactory fit for the total Hong Kong and mainland Chinese sample. Significant correlation was found between RCBS-TC and CHRS (r=0.473). Findings also showed 14% of participants exhibited compulsive buying behavior. This study provides sufficient proof of the reliability and validity of RCBS-TC and CHRS. Their relationship was explored based on two sets of sample from different regions in Asia, which contributes more applicability in cross-cultural context.